A novel methodology for the rapid identification of the water diffusion coefficients of composite materials. (January 2015) - Beringhier, M.; Gigliotti, M.
Abstract: The paper presents a novel methodology for the rapid identification of the water diffusion coefficients of composite materials. The methodology consists in employing a numerical parametric Proper Generalized Decomposition (PGD) method allowing incorporating the diffusion coefficients among the number of degrees of freedom. Compared to classical identification schemes, often based on Finite Element Method (FEM) iterations, the proposed method allows achieving consistent CPU time gain. The method is general and can be applied when diffusion anomalies take place or when diffusion–reaction coupling must be taken into account, moreover can deal with anisotropic materials. However, for the scope of illustration, in the present case, it is applied to the simple case of "classical diffusion" (Fick's model with constant boundary conditions) and concerns isotropic materials.